47 FHIRworks 2020: an interoperability hackathon for a healthcare information exchange. (30th November 2020) - Visram, Sheena; Mohamedally, Dean; Bassi, Daiana; Bahadur, Usman; Stylianou, Costas; MacNamara, Jon; Winstanley, Tom; Quinn, Glen; Sebire, Neil J
Abstract : Introduction: Interoperability in healthcare is a fundamental principle for scalable deployment of novel tools. Fast Healthcare Interoperability Resources (FHIR) comprise data specifications and an application processing interface (API) for the secure exchange of electronic health records (EHR). GOSH DRIVE together with UCL Computer Science and the National Framework of IXNs (Industry Exchange Network) has supported the integration and mainstreaming of standards that make healthcare systems interoperate. Here we present an interoperability hackathon and resulting catalogue of prototypes built using the latest R4 FHIR for healthcare. Method: During February 2020, a two-day hackathon with UCL CS and GOSH DRIVE tasked computer science students with 15 broad challenges to explore FHIR for healthcare. Solutions were built using a synthetic patient record testbed. This testbed offered a FHIR API access allowing connection to any developer environment and technology stack. Mentorship was provided to students by Microsoft, Aridhia, IBM, Intel, EMIS and NTT Data. Results: The GOSH FHIRworks 2020 Hackathon saw 129 FHIR open source demonstrators being built for GOSH DRIVE and the NHS. Exploratory prototypes included smart letter generaters (28), graphical data visualisations (37), and also a breadth of smart watches, scanners, chatbots and AR/VR demonstrators. This included automated video conferencing over Skype and MS Teams, filtered FHIR data aggregated on Google Maps to visualise patient demographics and immersive solutions that conceptualised patient FHIR records as holograms. Conclusion: As part of the GOSH DRIVE vision to accelerate the deployment of cutting-edge technologies, we have demonstrated effective use of synthetic patient datasets through FHIR APIs to conduct interoperability hackathons. As a next step, these FHIR solutions will be hosted in a demonstrator suite on site to introduce FHIR principles and capabilities to staff at GOSH. We believe that such NHS partnerships with academia facilitate the advancement of safe and secure future healthcare information exchanges.